Performance Evaluation of Secure Key Distribution Based on Quantum Mechanics Principles Over Free Space (International Journal of Engineering and Computer Science, 2014)
Quantum key distribution (QKD) provides a perfectly secure coding method which solves the problem of key distribution, it is currently the most mature application in the field of quantum computing. Performance analysis is very important in determining the effectiveness of various QKD protocols. However, Lack of effective simulation tools for evaluating QKD protocols over free space results to use of Analytical (theoretical) and experimental (real equipments) for evaluation, the later is inaccurate while the former is expensive. Optisystem 7.0, a commercial photonic simulator which is widely used in telecommunication was used in modeling and simulating BB84,B92 and Six State QKD protocols. The simulation model emphasizes on the experimental components of quantum key distribution. Results obtained based on the sifted key rate and failure rate shows that Six state protocol has a low sifted key rate and high failure rate which are identical to results from experiments. Lack of detector implementation and assumption of the single photon reduces the accuracy of the results. The simulation can help researchers to test their models before performing experiments.